Analisis Perhitungan Overall Equipment Effectiveness (OEE) Untuk Peningkatan Nilai Efektivitas Mesin Sewing Line 10 Pada PT. PAN Brothers - Arum Fauzan Nur Syamsi (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
Developments in the world of manufacturing industry are increasing, very tight industrial competition is encouraging industry to increase production effectiveness. PT. PAN Brothers is a manufacturing industry located in Boyolali, Central Java. PT. PAN Brothers produces clothing types such as jackets, coats, ski jackets, down jackets, tracksuits, travel pants and so on. During the production process, sewing machines have problems, namely machine damage. This research aims to analyze the effectiveness of sewing machine performance using the Overall Equipment Effectiveness (OEE) method and provide suggestions for improving the results of the Failure Mode and Effect Analysis (FMEA) method. The measurement uses the OEE method with three main components, namely availability rate, performance rate and quality rate to identify types of losses based on the six big losses. The average OEE value of 60% is still below world class standards with factors influencing the low OEE value. namely the performance rate, while the losses that affect the effectiveness value of the performance rate are Idling and minor stoppages losses with a value of 42%. By carrying out root cause analysis using a fishbone diagram, the root causes of low performance values ​​influenced by Idling and minor stoppage losses are known, namely machine factors, human factors, methods, materials and the environment. After identifying the problem and measuring the Risk Priority Number (RPN), suggestions for improvement were obtained including providing training to operators, to implement a preventive maintenance system, adding employees in the line balancing section and adding equipment to support machine repair facilities.